2011
DOI: 10.1051/0004-6361/201116515
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of protoplanetary dust growth: pebbles, boulders, or planetesimals?

Abstract: Context. The evolution of dust particles in protoplanetary disks determines many observable and structural properties of the disk, such as the spectral energy distribution (SED), appearance of disks, temperature profile, and chemistry. Dust coagulation is also the first step towards planet formation. Aims. We investigate dust growth due to settling in a 1D vertical column of a disk. It is known from the ten micron feature in disk SEDs, that small micron-sized grains are present at the disk atmosphere throughou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
180
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(190 citation statements)
references
References 50 publications
(37 reference statements)
10
180
0
Order By: Relevance
“…A second point which should be addressed is the single porosity of our samples (φ ∼ 0.37). Various numerical simulations (Suyama et al 2008;Zsom et al 2011;Okuzumi et al 2012) have shown that the first dust agglomerates might have had a much lower volume filling factor (down to φ ∼ 10 −3 ). Zsom et al (2011) showed that particles with a mass of ∼ 10 −6 g can still have such a low density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second point which should be addressed is the single porosity of our samples (φ ∼ 0.37). Various numerical simulations (Suyama et al 2008;Zsom et al 2011;Okuzumi et al 2012) have shown that the first dust agglomerates might have had a much lower volume filling factor (down to φ ∼ 10 −3 ). Zsom et al (2011) showed that particles with a mass of ∼ 10 −6 g can still have such a low density.…”
Section: Discussionmentioning
confidence: 99%
“…Various numerical simulations (Suyama et al 2008;Zsom et al 2011;Okuzumi et al 2012) have shown that the first dust agglomerates might have had a much lower volume filling factor (down to φ ∼ 10 −3 ). Zsom et al (2011) showed that particles with a mass of ∼ 10 −6 g can still have such a low density. Their simulations also showed that, after a relatively short time (few hundred years), these particles can become more compact and end with values comparable to our samples.…”
Section: Discussionmentioning
confidence: 99%
“…The Monte Carlo coagulation algorithm with equal-mass representative particles -makes it easy to implement additional particle properties, such as porosity (Zsom & Dullemond 2008;Zsom et al 2010), because the computation time does not depend significantly on the number of properties that are evolved, but only on the number of collisions performed; -is straightforward to develop to further spatial dimensions (Zsom et al 2011;Drążkowska et al 2013), as the representative particles can be treated as Lagrangian tracer bodies; -can be used along with hydrodynamic grid codes (Johansen et al 2012); -experiences no numerical diffusion of the mass function in general, so there is no danger of encountering an artificial speed-up of the growth; -has difficulty resolving features that include low fraction of total mass, which makes it less useful in the case of breaking through the growth barriers or runaway growth modeling, although the algorithm can be developed to overcome this issue (Ormel & Spaans 2008), -makes it hard to model evolution over long timescales in general, because it is impossible to use extremely long timesteps, as every collision needs to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of grains with Stokes number of order unity and dust-to-gas ratios of order unity (ie.. ǫ ≃ 0.5) is expected (e.g. Barrière-Fouchet et al 2005;Zsom et al 2011). In such a situation, the right panel of Fig.…”
Section: Outward Migration Of Dust Particlesmentioning
confidence: 99%